Functional and Structural Characterization of Francisella tularensis O-Antigen Antibodies at the Low End of Antigen Reactivity - Lu, Zhaohua (Mary Ann Liebert, Inc., 2014)
The O-antigen (OAg) of the Gram-negative bacterium Francisella tularensis (Ft), which is both a capsular polysaccharide and a component of lipopolysaccharide, is comprised of tetrasaccharide repeats and induces antibodies mainly against repeating internal epitopes. We previously reported on several BALB/c mouse monoclonal antibodies (MAbs) that bind to internal Ft OAg epitopes and are protective in mouse models of respiratory tularemia. We now characterize three new internal Ft OAg IgG2a MAbs, N203, N77, and N24, with 10- to 100-fold lower binding potency than previously characterized internal-OAg IgG2a MAbs, despite sharing one or more variable region germline genes with some of them. In a mouse model of respiratory tularemia with the highly virulent Ft type A strain SchuS4, the three new MAbs reduced blood bacterial burden with potencies that mirror their antigen-binding strength; the best binder of the new MAbs, N203, prolonged survival in a dose-dependent manner, but was at least 10-fold less potent than the best previously characterized IgG2a MAb, Ab52. X-ray crystallographic studies of N203 Fab showed a flexible binding site in the form of a partitioned groove, which cannot provide as many contacts to OAg as does the Ab52 binding site. These results reveal structural features of antibodies at the low end of reactivity with multi-repeat microbial carbohydrates and demonstrate that such antibodies still have substantial protective effects against infection.